PERANCANGAN AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN ANAK - M. Rizqi Hidayah Adryansyah; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
Augmented Reality (AR) is a technology that displays the real world with virtual objects by combining two-dimensional and three-dimensional virtual objects into a three-dimensional real environment and then projecting them in real time. Augmented Reality (AR) can be used to design applications as a medium for children's learning. With the use of AR, of course, it will provide an interactive and real-time atmosphere so as to increase children's interest and interest in learning. Therefore the researchers carried out Augmented Reality Design as a Children's Learning Media. To carry out this research, researchers used the Multimedia Development Life Cycle (MDLC) method. Also, by using several tools and in the form of Laptop/Computer and Smartphone Hardware with software such as Vuforia, Photoshop, WAV, Figma and Unity 3D. With the results of the research in the form of applications that utilize Augmented Reality as Children's Learning Media regarding the introduction of surrounding objects.